ANALISIS TOTAL MIKROBA, BAHAN ORGANIK DAN RESPIRASI TANAH PADA LAHAN APLIKASI DAN TANPA APLIKASI TANDAN KOSONG KELAPA SAWIT - Sakiah Sakiah; Muhammad Yusuf Dibisono; Reza Ikbal Irawan (Jurnal Agro Estate, 2018)
This study aims to determine the total microbes, organic matter and soil respiration on application land and without the application of empty fruit bunches. The research was conducted at Begerpang, PT. London Sumatera as the location for taking soil samples, the soil is analyzed in the Soil Biology Laboratory of the Faculty of Agriculture, USU and the Soil and Fertilizer Laboratory, STIP-AP which runs from May to September 2018. The study used Factorial Randomized Block Design, consisting of two factors. Factor 1: sampling area, Factor depth of sampling from ground level. The results showed the average microbial total on the application of oil palm empty fruit bunches 17,05 CFU / ml, organic matter 7,25% and soil respiration 3,18 mg CO2 while on land without the application of oil palm empty bunches the total microbial 3,55 CFU / ml, organic matter 5,07% and soil respiration 2,75 mg CO2. The average total microbes, organic matter and soil respiration is highest at a depth of 0-10 cm. Total microbes are positively correlated with organic matter and soil respiration, the correlation coe cient between total microbes and organic matter is 0.977, between total microbes and soil respiration 0.868 .